The Potential of Sitka Spruce Bark as an Alternative to Peat Casing for Mushroom (Agaricus bisporus) Production - Gabrielle Young; Helen Grogan; Eoghan Corbett; Brian W. McGuinness; Michael T. Gaffney; Saoirse Tracy; Olaf Schmidt; Lael Walsh (Horticulturae)
White button mushrooms are an important crop globally, and due to the role of peat in current cultivation practices, the industry is under increasing pressure to find suitable alternatives. Peat functions as “casing”, a surface layer that, amongst other functions, provides available water to the fungal mycelium and is considered essential for mushroom growth. This research aimed to determine the potential of bark as an alternative casing material and its suitability for commercial mushroom production. Two experiments were conducted, comparing two types of commercially available peat casing with bark-based casings. The bark casing in Experiment A was found to be statistically similar to the peat casing in terms of yield and quality. The two bark casings in Experiment B failed to produce a 1st flush of mushrooms, and total yields were significantly lower compared to the peat casings, highlighting the fact that the consistency of the bark material across both experiments was variable. There were several issues associated with the bark casing, which included water stress and cropping delays, all of which would be unacceptable from a commercial perspective. Further research is required to refine bark-based casing, focusing on a better consistency of the bark feedstock and reduction of contamination risk. This work contributes to ongoing research and development to address the dependency of mushroom production on peat.